The direct anterior or direct lateral approach for simultaneous bilateral total hip arthroplasty: A functional recovery and in-hospital cost analysis - Benaroch, Lee R; Moody, Patrick W; Marsh, Jacquelyn D; Vasarhelyi, Edward M; Somerville, Lyndsay; Lanting, Brent A (Journal of orthopaedics, trauma and rehabilitation, 2025)
Background: Simultaneous bilateral total hip arthroplasty (sbTHA) has been demonstrated to be an excellent option for medically fit patients. To our knowledge, no previous studies have compared differences in patient-reported outcome measures (PROM) and costs of sbTHA performed via the direct anterior (DA) or direct lateral (DL) approaches. Methods: We performed a retrospective cohort analysis of patients at our institution who underwent sbTHA between 2006 and 2020 with a minimum 1-year follow-up. Functional outcomes were assessed using the Harris Hip Score, the Western Ontario MacMaster Arthritis Index, and Veteran RAND 12 Item Health Survey scores preoperatively and at 1 year postoperatively. Limb length and combined offset discrepancy were assessed on the first standing postoperative radiograph. Perioperative costs were compiled from charts and adjusted for inflation before cost analysis. Results: A 2:1 match for age and sex selected 34 DA and 17 DL subjects. Diagnoses were similar among groups. The DA group had a significantly lower body mass index (26.99 vs. 32.61, p = 0.0009). There was no difference in the change in PROM or radiographic measures at 1-year postoperatively between groups. The DA group demonstrated significantly lower reported limp (8.3% vs. 46.2%, p = 0.013), procedure time (125.74 vs. 156.41 min, p < 0.001), operating room time (165.68 vs. 194.59 min, p = 0.005), length of stay (1.97 vs. 6.65 days, p < 0.001), and rehab discharge (11.8% vs. 47.1%, p = 0.012). Total perioperative costs were significantly less for the DA group (CAD 13,699.37 vs. CAD 18,491.82), with a mean difference of CAD 4792.45 ( p < 0.001). Conclusion: The DA approach showed reduced length of stay and surgical time, resulting in lower perioperative costs. PROM showed no difference; however, DA patients were less likely to have a limp 1-year postoperatively. Thus, the DA approach may lead to a better gait and lower costs for those undergoing sbTHA.